POST-COVID DIGITAL TRANSFORMATION IN ISLAMIC BOARDING SCHOOLS: RETHINKING QUALITY MANAGEMENT FOR RESILIENT ISLAMIC EDUCATION - Suryana, Aep Tata (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
The COVID-19 pandemic has triggered drastic changes in the education system, including in Islamic boarding schools that have relied on traditional approaches. Islamic boarding schools face significant challenges in maintaining educational continuity amid limited access to resources, inadequate infrastructure, and limited digital competence. These changes require rapid adjustments that are not only technical but also involve institutional aspects and the basic values ​​of Islamic education. This study aims to analyze how post-pandemic digital transformation drives the reorientation of Islamic education quality management in Islamic boarding schools. The method used is a qualitative approach with data analysis sourced from literature studies and relevant documents that are reviewed thematically. The collected data are analyzed reflectively to explore the response of Islamic boarding schools to the crisis and adaptation to maintaining the quality of education. The results of the study show that Islamic boarding schools carry out various emergency innovations and structural adjustments despite facing limited infrastructure and digital competence. This adaptation is supported by responsive leadership and internal creativity in managing change. These findings emphasize the importance of adaptive leadership and quality management renewal as a foundation for building resilient Islamic education resilience in the future.